Reciclagem de sucata de jóias para a recuperação hidrometalúrgica de ouro e prata - Carol Elizabeth Barrientos Rojas (2009)
A great amount of scrap metal wastes away in the manufacturing of gold jewelry, which due the lack of knowledge of precious metals recovery used in its manufacturing. A part of this scrap material is considered as a high-grade scrap of gold, silver and platinum metals. In this Master degree Thesis it has been evaluated the use of a hydrometallurgical methodology to treat scrap gold jewels. The methodology consisted of an initial leaching of samples with proportions higher (sample A) and lower than 10% Ag (sample B) with HNO3 to extract silver, followed by aqua regia leaching to extract gold from the solid residue of the previous stage. The complete Factorial Method was used with two experimental levels to evaluate the influence of the variables on the experimental response: leaching time, aqueous leaching solution temperature and solid/liquid ratio, on the metallic extraction percentage. The optimization statisticalmethod of the ascending step was used after the factorial method aiming at determining the optimum experimental conditions to reach the maximum gold and silver extraction percentage. For the silver recovery, the liquors from leaching with HNO3 were used, and the following methods were evaluated: cementation with zinc powder, precipitation with FeSO4 and AgCl calcination. For the gold recovery, the aqua regia liquors were treated by the methods: cementation with zinc powder and precipitation with FeSO4. The final results for the hydrometallurgical methodology adopted by the gold and silver recovery from 10k jewel scrap were: Optimum conditions for total Ag and Cu leaching with HNO3: 32ml of HNO3, 1.5 h and 42°C for sample A and 45ml of HNO3, 2.25h and 43°C for sample B; Optimum conditions for total Au leaching with aqua regia from the solid residue of previous leaching: 0.140g of gold solid residue, 0.85h and 43°C for sample A, and 0.056g of gold solid residue, 0.78h and 43°C for sample B; AgCl calcination to recovery 94% of Ag (940 millesimals), being Au and Sn the main impurities with content nearly to 2% each; Precipitation with FeSO4 recovered 98.7% of Au (23.7k), being Ag the main impurity with content of 0.72%.